Energy Efficiency and Electricity Reliability - Carranza, Eliana; Meeks, Robyn (The Review of Economics and Statistics, 2021)
Overloaded electrical systems are a major source of unreliable power. Using a randomized saturation design, we estimate the impact of compact fluorescent lamps (CFLs) on electricity reliability and household electricity consumption in the Kyrgyz Republic. Greater saturation of CFLs within a transformer leads to fewer outages, a technological externality benefiting all households, regardless of individual adoption. Spillovers in CFL adoption further reduce electricity consumption, contributing to increased reliability within a transformer. CFLs' impacts on household electricity consumption vary according to the effects on reliability. Receiving CFLs significantly reduces electricity consumption, but increased reliability permits greater consumption of electricity services.